India in World Affairs : The Next Decade - Azam, Kousar J. (Brill | Manohar Publishers & Distributors, 2016)
It is very evident that much of the scholarly work currently done in the field of defence, human resources, strategic and development studies converges on issues which impact international relations both in policy formulation and its implementation through bilateral or multilateral arrangements. Issues such as Energy, Environment, Disaster Management, Technology, Food, Agriculture, Poverty, Health, Refugees, Migration, Trade, Political Formations among others, are now increasingly influencing global decision-making. The Osmania Universiy Centre for International Programmes-OUCIP had organized an international conference to reflect on these issues. The present volume is an edited collection of the papers presented at the conference. Divided into nine parts, the essays deal with India's reach, role and responsibility as a soft power, her relations with immediate neighbours as well as the big powers in the decades ahead. It also includes essays on India's influence and contribution to regions like Africa, Middle East and Asia-Pacific as well as her ability to tackle the issues like Food, Water Energy, and so on in her interactions with world community. Analysing the multiple dimensions of India's foreign relations this collection will be invaluable for students and scholars of international relations and strategic studies.